PENGARUH TATA KELOLA PERUSAHAAN TERHADAP EFISIENSI MODAL INTELEKTUAL - Salsabillah Shafa; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the influence of corporate governance mechanisms on effeciency intellectual capital (IC). Drawing on the agency theory, the study develops hypothesis about relationship between corporate governance mechanism (such as board size, board composition, the level of independence of audit committee and the level of independence of remuneration commmitte) and intellectual capital (IC). The population of this study consists of all service firms listed on Indonesian Stock Exchange in 2016-2018 following the exclusion of financial institution (e.g banks, insurance,and others). Sample of this study is obtained by using puprosive sampling method and the final sample in this research is 168 samples for the period 2016-2018. The study uses a multiple regression analysis. The results of this study show that not all corporate governance mechanisms which be used in this reseacrh have significant association with efficiency of intellectual capital.